INTEGRASI PEMBELAJARAN STEM PADA MATERI MORFOLOGI TUMBUHAN DI SEKOLAH MENENGAH ATAS: SEBUAH SCOPING REVIEW - Jayanto, Pery (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study aims to map the various contexts and implementation steps of STEM (Science, Technology, Engineering, and Mathematics) education in teaching plant morphology at the senior high school level. A scoping review method was employed, examining a range of national publications published between 2021 and 2025. The review followed the framework proposed by Arksey and O’Malley, which includes five stages: (1) identifying the research question, (2) identifying relevant studies, (3) study selection, (4) charting the data, and (5) collating, summarizing, and reporting the results. The search utilized a combination of keywords such as “Pembelajaran STEM,” “Morfologi Tumbuhan,” and “Sekolah Menengah Atas.” Data analysis was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The review findings indicate a high urgency for integrating STEM approaches into plant morphology instruction, particularly in addressing the demands of 21st-century education, including the development of critical thinking, creativity, collaboration, and scientific literacy. The learning contexts identified involve the use of interactive modules, digital media with graphical content, e-books, and the development of instructional materials incorporating local content. Furthermore, the instructional steps of STEM-based learning were systematically designed using models such as 4D and ADDIE and were implemented through Project-Based Learning and Inquiry-Based STEM models. The learning process includes problem identification, exploration, solution design, project implementation, and evaluation. These findings underscore the potential of STEM integration in enhancing the quality of learning processes and the mastery of biological concepts in a more applicable and meaningful manner. Therefore, STEM integration is strongly recommended as an innovative approach to biology instruction at the senior high school level. ABSTRAK Penelitian ini bertujuan untuk memetakan berbagai konteks dan langkah-langkah implementasi pembelajaran STEM (Science, Technology, Engineering, and Mathematics) pada materi morfologi tumbuhan di jenjang Sekolah Menengah Atas (SMA). Metode yang digunakan adalah scoping review dengan menelaah berbagai literatur nasional terpublikasi antara tahun 2021 hingga 2025 dengan tahapan yang mengadopsi dari Arksey dan O'Malley, yang terdiri dari lima tahap: (1) identifikasi pertanyaan penelitian, (2) identifikasi studi yang relevan, (3) seleksi studi, (4) charting data, dan (5) penyusunan, pengkajian, dan pelaporan hasil. Kata kunci yang digunakan dalam pencarian meliputi kombinasi istilah seperti “Pembelajaran STEM,” “Morfologi Tumbuhan”, dan “Sekolah Menengah Atas”. Análisis data menggunakan kerangka Preferred Reporting of Items for Systematic Review and Meta-Analysis (PRISMA). Hasil kajian menunjukkan bahwa integrasi pembelajaran STEM dalam materi morfologi tumbuhan memiliki urgensi tinggi dalam menjawab tuntutan pendidikan abad ke-21, khususnya dalam pengembangan keterampilan berpikir kritis, kreatif, kolaboratif, dan literasi sains. Konteks pembelajaran yang diimplementasikan mencakup penggunaan modul interaktif, media digital berbasis grafik, e-book, serta pengembangan perangkat ajar dengan muatan lokal. Sementara itu, langkah-langkah pembelajaran STEM dirancang secara sistematis menggunakan model pengembangan seperti 4D dan ADDIE, serta diterapkan melalui model Project-Based Learning dan Inquiry-Based STEM. Proses pembelajaran melibatkan identifikasi masalah, eksplorasi, perancangan solusi, pelaksanaan proyek, dan evaluasi. Temuan ini menegaskan bahwa pembelajaran STEM dalam materi morfologi tumbuhan berpotensi meningkatkan kualitas proses belajar serta penguasaan konsep biologi secara lebih aplikatif dan bermakna. Dengan demikian, integrasi STEM sangat direkomendasikan sebagai pembelajaran inovatif dalam pembelajaran biologi di tingkat SMA.